Transformative Economic Challenges: The Impact of COVID-19 and the War in Ukraine on the European Union - Todorov, Ivan; Angelova, Gergana; Aleksandrov, Aleksandar (Naše gospodarstvo/Our economy, 2024)
This paper aims to explore the economic effects of the COVID-19 pandemic and the war in Ukraine on the twenty-seven European Union (EU) member states, known as the EU-27. A vector autoregression (VAR) of quarterly data for the period 2020–2022 was employed to study the impact of the coronavirus and the Russian invasion of Ukraine on growth, unemployment and inflation in the EU-27. The results from the empirical analysis indicated that the war in Ukraine lowered growth and raised inflation and unemployment, while the COVID-19 pandemic did not affect growth, increased unemployment and decreased inflation in the EU-27. It may be concluded that the war in Ukraine shifted the EU aggregate supply curve to the left, whereas the coronavirus pandemic resulted in inflation-unemployment trade-off in the EU.